The effect of captopril on membrane bound enzymes in ischemia-reperfusion injury - (:unkn) unknown (ELSEVIER SCI LTD, 2000)
There is substantial evidence that Na+K+/Mg2+ ATPase and Ca2+/Mg2+ ATPase enzymes would effect the membrane integrity. Forty guinea pig (n = 10 in each group) hearts were studied in an isolated Krebs-Henseleit solution perfused Langendorff cardiac model. The first group was utilized as the control group. Group 2 hearts were arrested with captopril (200 mu mol/l) added St Thomas Hospital Cardioplegic Solution (STHCS). Group 3 animals were pretreated with oral captopril (0.3 mg/kg/twice a day) for 10 days and then arrested with STHCS. Group 4 hearts were again pretreated with oral captopril (0.3 mg/kg/twice a day for 10 days) arrested with STHCS and reperfused with captopril added Krebs-Henseleit solution (200 mu mol/l). Hearts were subjected to normothermic global ischemia for 90 min and than were reperfused at 37 degrees C. When the treated groups were compared with control, best results were achived by group 4. The Na+K+ and Ca2+/Mg2+ ATPase levels increased from 466.38 +/- 5.99 to 564.13 +/- 7.77 and 884.69 +/- 9.13 to 1254.29 +/- 5.75 nmol Pi/mg/prot/h respectively (P < 0.05). These results suggest that captopril protects the membrane integrity and thus played a role at the recovery of depressed membrane bound Na+K+/Mg2+ ATPase and Ca-2 (+)/Mg2+ ATPase activity and also in ischemia-reperfusion injury. (C) 2000 The International Society for Cardiovascular Surgery. Published by Elsevier Science Ltd. All rights reserved.
Keywords: captopril; cardioplegia; Ca2+/Mg2+ ATPase; myocardial protection; Na+K+/Mg2+ ATPase; ischemia-reperfusion injury; FREE-RADICALS; MYOCARDIUM; INHIBITORS; ATPASE; SYSTEM; CA-2+; CELLS